Historical Analysis of Population Migration - Akbarjonovich, Mansurov Abdulaziz (Research Parks Publishing LLC, 2023)
Considering the fact that migration is related not only to the social sphere, but also to other branches of science, it is becoming more relevant in the era of globalization. Attention is paid to the analysis of the reasons for the historical occurrence of migration, the consideration of the increasing and decreasing tendencies of the process at certain times, and its positive, negative effects, its political influence on the social life, of a certain region, country, area.